2022
DOI: 10.3389/fonc.2022.777367
|View full text |Cite
|
Sign up to set email alerts
|

Serum Free Fatty Acids and G-Coupled Protein Receptors Are Associated With the Prognosis of Epithelial Ovarian Cancer

Abstract: PurposeFatty acid metabolism plays key role in cancer development, and free fatty acid receptors (FFARs) are involved in many cancers. However, the correlation between serum free fatty acids (FFAs)/FFARs levels and ovarian cancer (OC) prognosis remains largely unclear.MethodsA retrospective review of 534 primary OC patients and 1049 women with benign ovarian tumors was performed. Serum FFA levels data were extracted from the electronic medical record system. Repeated FFA results of 101 OC patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In our study, the proportions of the etomoxir-sensitive respiration decreased in ascites-treated ovarian cancer cells, suggesting a decreased proportion of fatty acid degradation in cellular oxidative metabolism. Fatty acid metabolism is associated with ovarian cancer growth [65][66][67][68][69][70][71]. Importantly, a recent report [72] showed that the inhibition of CPT2 strongly supported metastasis formation and poor prognosis in a pool of human ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the proportions of the etomoxir-sensitive respiration decreased in ascites-treated ovarian cancer cells, suggesting a decreased proportion of fatty acid degradation in cellular oxidative metabolism. Fatty acid metabolism is associated with ovarian cancer growth [65][66][67][68][69][70][71]. Importantly, a recent report [72] showed that the inhibition of CPT2 strongly supported metastasis formation and poor prognosis in a pool of human ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence have clari ed that FFA levels are associated with adverse cardiovascular events and play a role in the process of disease progression (Fatima et al 2019). Over the past few years, several studies have shown that a high FFA level was an independent risk factor for several types of malignancy, such as lung cancer, gastric cancer, thyroid cancer, colon cancer, rectal cancer, ovarian cancer (Zhang et al 2020b(Zhang et al , 2022. Recently, a retrospective analysis of 1049 cases of breast cancer indicated that BMI was an independent prognostic factor for BC, and had a U-shaped relationship with OS and breast cancer-speci c survival (BCSS) (Wei et al 2023).…”
Section: Introductionmentioning
confidence: 99%